ByzRev 03.2021.035: Ilias Taxidis, The Ekphraseis in the Byzantine Literature of the 12th Century: (Hellenica 90). Alessandria: Edizioni dell’Orso 2021. - Tomadaki, Maria (The Byzantine Review, 2021)
Ilias Taxidis, The Ekphraseis in the Byzantine Literature of the 12th Century (Hellenica 90). Alessandria: Edizioni dell’Orso 2021. XXXVI, 276 pp. – ISBN: 978-88-3613-077-1. ISSN: 1825-3490 (€ 42.00)